Aesthetic values ​​in presentations Circular theatre Reading in the Iraqi experience (Journal of the College of Basic Education, 2022)
There were many methods and forms of theatrical performances since the emergence of theatrical art until the present day, but the circular theater was the first geometric form known to man, and as a result of the emergence of Christianity and the fall of Rome, this type of theater receded in the church for a long time, and in the Renaissance era the theater came out of the church to return to its real incubator (common people), so the frame theater or what is called (the box) appeared, and after the outbreak of the two world wars (the first and the second), those in charge of the performing arts began to search for new places. The return to the circular theater was one of those places that approached the recipient and simulated his daily concern, and dealt with the problems left by the wars. The two researchers found that the title of his research should be (aesthetic values ​​in circular theater shows), and they divided their research according to the following: